Evaluating management and orchestration impact on closed‐loop orchestration delay. (23rd September 2020) - García‐Rois, Juan; Fondo‐Ferreiro, Pablo; Gil‐Castiñeira, Felipe; González‐Castaño, Francisco J.; Candal‐Ventureira, David
Summary: Network "softwarization" is enabling new features such as detecting the risk to violate a Service Level Agreement (SLA) and performing the required automated control actions on a network slice. A real‐time Network Function Virtualization (NFV) Management and Orchestration (MANO) system should detect any SLA degradation and act to recover the SLA. The closed‐loop automation approach monitors the state of the network and triggers policy‐based control actions when needed. The delay between the detection of an SLA issue and the completion of a correcting action is critical for satisfying latency‐related SLAs. Thus, in this article we propose this delay as a new key performance indicator (KPI) for NFV MANO systems, which we call Closed‐Loop Orchestration Delay (CLOD). CLOD is subdivided into independent time intervals that depend on the NFV MANO platform, the target Virtualized Infrastructure Management (VIM) and the target virtual network function (VNF) software. CLOD is evaluated on a real use case: a latency‐sensitive elastic network slice in which Internet user round‐trip time (RTT) is monitored. When the service level of the slice drops below a predefined limit a new data plane is deployed near the user reducing latency. In the evaluation, we considered two approaches: (i) a general implementation of the NFV MANO architecture based on the Open Network Automation Platform (ONAP) and OpenStack and (ii) an optimized ad‐hoc baseline implementation to minimize CLOD. We provide the details of both implementations and compare their CLODs leading to useful insights for the NFV MANO community.